Illustrated Chronicle Manuscripts of the 15th Century: Problems of the Research and Interpretations - Piven, Marina G. (Actual Problems of Theory and History of Art, 2021)
The article focuses on the research problems of the Illustrated Chronicles manuscripts: illustrative versions, created in the 15th century and their later copies. This complex includes, ascending to a single source, the so-called “The Crespi Chronicle”, fragmentarily known “Cockerell Chronicle”, an album titled “Libro di Giusto”, and the “Florentine Pictures-Chronicle”, which became a development of the manuscripts’ illustrative program. The author outlines the key aspects of the history of these pieces and detects the main problems associated with their studying and interpretation: the difficulties in attribution, the general typology of that kind of works, their functional purpose and the audience perception, as well as the features of the iconography of illustrative cycles, the literary sources underlying their program, and the connection with the lost cycle of murals “Uomini Famosi” in the Roman palace of Cardinal Giordano Orsini.
Keywords: Picture-Chronicle manuscripts; humanistic themes in art; Cockerell Chronicle; Crespi Chronicle; Florentine Picture-Chronicle; historiography of Renaissance art